Analisis Daya Saing Ekspor Kopi Indonesia Di Pasar Internasional - Felicitas Parnadi dan Riris Loisa (Universitas Tarumanagara, 2019)
This study aims to analyze and know how the level of competitiveness of Indonesian coffee exports in the International Market. The study was conducted using secondary data from various sources, including from BPS (BPS, 2016), Indonesian Ministry of Agriculture, International Coffee Organization, 2016) and AEKI (2016). Secondary data used in the form of time series data in the period of 7 years (2010-2016). Coffee is the object of research is all types of coffee. The data analysis method uses quantitative analysis method which is used to analyze the level of competitiveness of Indonesian coffee commodity exports in international market which include: Revealed Comparative Advantage (RCA), Import Dependency Ratio (IDR), and Index of Market Specialization (ISP). Data processing will be done using Microsoft Excel 2013 software.Based on the analysis of Revealed Comparative Advantage (RCA) value, from 2010-2016 of 3.57, Indonesia has a comparative advantage in the coffee trade in the international market. However, the comparative advantage of Indonesia is still low compared to Colombia, Vietnam and Brazil, although still higher than India. The level of dependence on Indonesian coffee imports is calculated by using Import Dependency Ratio (IDR) of 1.42 percent. Indonesian coffee has a high competitiveness, as the value of the Indonesian Trade Specialty Index (ISP) of 0.91. This indicates that Indonesia is an exporting country for coffee commodities. Positive ISP results greater than 0 indicate that Indonesia's coffee commodity has a strong competitiveness, because the value of Indonesian coffee exports is greater than the value of Indonesian coffee imports.